Axillary ultrasound and sentinel lymph node biopsy: an evolving paradigm for management of the axilla. (May 2014) - Cyr, Amy E; Margenthaler, Julie A
SUMMARY : Axillary lymph node dissection was used to treat and to provide staging information for women with invasive breast cancer. With the adoption of sentinel lymph node biopsy over the past two decades, evaluation and management of the axilla has become less invasive for many patients. However, as treatment decisions are more frequently based on tumor biology rather than anatomic staging information, the information obtained from even more minimal axillary surgery may be less clinically relevant, and any surgery may cause morbidity. Imaging technologies, such as axillary ultrasound, offer the capability of providing some staging information without the risks associated with surgery. In addition, the therapeutic need for axillary surgery is in question, and less invasive means of managing the axilla are under investigation.